Double-Stranded-RNA-Activated Protein Kinase PKR Enhances Transcriptional Activation by Tumor Suppressor p53 - Cuddihy, Andrew R. (American Society for Microbiology, 1999)
The tumor suppressor p53 plays a key role in inducing G(1) arrest and apoptosis following DNA damage. The double-stranded-RNA-activated protein PKR is a serine/threonine interferon (IFN)-inducible kinase which plays an important role in regulation of gene expression at both transcriptional and translational levels. Since a cross talk between IFN-inducible proteins and p53 had already been established, we investigated whether and how p53 function was modulated by PKR. We analyzed p53 function in several cell lines derived from PKR(+/+) and PKR(−/−) mouse embryonic fibroblasts (MEFs) after transfection with the temperature-sensitive (ts) mutant of mouse p53 [p53(Val135)]. Here we report that transactivation of transcription by p53 and G(0)/G(1) arrest were impaired in PKR(−/−) cells upon conditions that ts p53 acquired a wild-type conformation. Phosphorylation of mouse p53 on Ser(18) was defective in PKR(−/−) cells, consistent with an impaired transcriptional induction of the p53-inducible genes encoding p21(WAF/Cip1) and Mdm2. In addition, Ser(18) phosphorylation and transcriptional activation by mouse p53 were diminished in PKR(−/−) cells after DNA damage induced by the anticancer drug adriamycin or γ radiation but not by UV radiation. Furthermore, the specific phosphatidylinositol-3 (PI-3) kinase inhibitor LY294002 inhibited the induction of phosphorylation of Ser(18) of p53 by adriamycin to a higher degree in PKR(+/+) cells than in PKR(−/−) cells. These novel findings suggest that PKR enhances p53 transcriptional function and implicate PKR in cell signaling elicited by a specific type of DNA damage that leads to p53 phosphorylation, possibly through a PI-3 kinase pathway.